Correlations of portal pressure in post‐cholecystectomy benign biliary stricture. Issue 10 (22nd January 2015) - Nag, Hirdaya H.; Arora, Asit; Tyagi, Ila; Ramaswamy, Dinesh; Patil, Nilesh; Sakhuja, Puja; Saha, Renuka; Agarwal, Anil K.
Abstract : Aim: Presence of portal hypertension (PH) adversely affects perioperative and long‐term outcome in patients with post‐cholecystectomy benign biliary stricture (PCBBS). Identification of factors related to the development of PH will help to prevent this complication. Methods: From September 2010 to December 2012, 30 patients with PCBBS were studied prospectively for correlation of portal pressure (PP) with injury repair interval (IRI), biliary pressure (BP), severity of hepatic fibrosis (FS), severity of hepatic inflammation (IS) and obstructive biliary pathology score (OBPS). Appropriate statistical methods employed and P ≤ 0.05 (two‐sided) was considered statistically significant. Results: Mean PP, mean BP and median IRI were 19.4 ± 4.74 mmHg, 20.1 ± 3.99 mmHg and 145 days, respectively. Spearman's rank correlation coefficients ( P‐ value) of PP with IRI, FS, IS and OBPS were 0.564 (0.001), 0.502 (0.004), 0.752 (0.0001) and 0.242 (0.19), respectively. Pearson correlation of PP with BP was r = 0.383 ( r 2 = 0.146, P = 0.03). Spearman's rank correlation coefficients ( P ‐value) of FS with IS and OBPS were 0.561 (0.003) and 0.371 (0.04), respectively. Spearman's rank correlation coefficient of serum bilirubin with OBPS was 0.550 ( P = 0.001). Incidence of PH was 33.3% and mean fall of PP following biliary repair was 6.2 ± 1.98 mmHg ( P < 0.0001). Conclusion: PP in patients with PCBBS has a good correlation with IS, and a fair correlation with both FS and IRI whereas PP was not directly related to BP and OBPS; further prospective trials are mandatory to confirm this correlation, and to evaluate mechanism of fall in PP following biliary decompression.